Comparative analysis of thrombocytopenia incidence in patients treated with generic vs. brand-name linezolid: a cohort study utilizing hospital electronic medical records - Wang, Zhizhou; Wang, Ke; Hua, Yiming; Hu, Xin; Zhang, Xiaotong; Li, Xiaoxi; Xing, Xiaoxuan; Feng, Yingnan; Wu, Chao; Zhang, Zhichao; Dong, Xianzhe; Zhang, Lan (Frontiers in Pharmacology, 2025)
BackgroundThis study aimed to evaluate the hematological safety of generic linezolid, providing data to support its rational and safe use in clinical practice.MethodsData were collected from electronic medical records at a tertiary hospital in China between January 2019 and June 2023. We conducted a real-world, retrospective matched cohort study involving hospitalized patients treated with either generic or brand-name linezolid for bacterial infections. Propensity score matching was employed to control for potential risk factors associated with thrombocytopenia. The primary outcome was the incidence of thrombocytopenia adverse events. Secondary outcomes included rates of severe thrombocytopenia, the incidence of anemia meeting transfusion thresholds, and changes in platelet counts (PLTs) and hemoglobin (Hb) levels during follow-up.ResultsA total of 218 patients received generic linezolid, while 222 patients received the brand-name version. After adjustment, each group had 137 patients. There were no significant differences in thrombocytopenia (28.44% vs. 21.17%), severe thrombocytopenia (6.42% vs. 4.95%), or anemia rates (2.75% vs. 3.15%) (P > 0.05). Similarly, reductions in PLT and HB levels during follow-up did not differ significantly (P > 0.05).ConclusionOur results indicate no significant differences in the incidence of thrombocytopenia and severe anemia between generic and brand-name linezolid, highlighting the need for further validation in other generic formulations and diverse patient populations.